1983
DOI: 10.1177/030098588302000411
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Virus-associated Respiratory Disease in Two Guinea Pigs

Abstract: Respiratory disease is a common cause of morbidity in the guinea pig, and is chiefly of bacterial origin [6, 71. Although a variety of viral diseases do occur in the guinea pig, there has been only one previous report of cavian respiratory disease associated with what was believed to be an adenovirus [6] and none reported in the U.S. We report here two cases of pneumonia associated with a virus morphologically similar to adenovirus.Two adult, female Hartley Crl:(HA/BR) guinea pigs being used in anthrax vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Adenoviridae: guinea pig adenovirus (GPAdV) BACKGROUND Virus-associated necrotizing bronchopneumonia in guinea pigs is a spontaneous multifactorial disease that has low morbidity, high mortality, and a worldwide distribution (Percy and Barthold, 2007). After the first description in Germany and experimental reproduction of the disease (Kunstyr et al, 1984;Naumann et al, 1981), sporadic spontaneous cases were reported from the United States, Australia, and Switzerland (Brennecke et al, 1983). A 10-year endemic "in-house" occurrence of adenovirus-associated disease was reported in a British pharmaceutical research facility.…”
Section: Dna Virusesmentioning
confidence: 99%
“…Adenoviridae: guinea pig adenovirus (GPAdV) BACKGROUND Virus-associated necrotizing bronchopneumonia in guinea pigs is a spontaneous multifactorial disease that has low morbidity, high mortality, and a worldwide distribution (Percy and Barthold, 2007). After the first description in Germany and experimental reproduction of the disease (Kunstyr et al, 1984;Naumann et al, 1981), sporadic spontaneous cases were reported from the United States, Australia, and Switzerland (Brennecke et al, 1983). A 10-year endemic "in-house" occurrence of adenovirus-associated disease was reported in a British pharmaceutical research facility.…”
Section: Dna Virusesmentioning
confidence: 99%
“…Adenovirus-induced respiratory disease with low morbidity and high mortality has been documented in guinea pigs [20][21][22][23][24]. Clinical signs range from those of pneumonia, including dyspnea, tachypnea, nasal discharge, rough hair coat, weight loss, and a hunched posture to acute death with no clinical signs.…”
Section: Respiratory Disease In Guinea Pigsmentioning
confidence: 99%
“…Entgegen den Ergebnissen von Brennecke (2), Breuer (3) und Naumann et al (35) waren in unserer Studie die Tiere wie bei Feldman (10) vorwiegend männlichen Geschlechts. Die lichtmikroskopischen Veränderungen entsprachen den in der Literatur beschriebenen Befunden (2,3,10,11,17,21,22,23,35). Entsprechend den Angaben anderer Untersucher (3, 10) konnten zwei verschiedene Typen von Viruspartikeln festgestellt werden.…”
Section: Diskussionunclassified